2019
DOI: 10.1186/s40104-019-0398-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary menthol-rich bioactive lipid compounds on zootechnical traits, blood variables and gastrointestinal function in growing sheep

Abstract: BackgroundThe present study aimed at investigating the influence of 90% menthol-containing plant bioactive lipid compounds (PBLC, essential oils) on growth performance, blood haematological and biochemical profile, and nutrient absorption in sheep. Twenty-four growing Suffolk sheep were allotted into three dietary treatments: Control (without PBLC), lower dose of PBLC (PBLC-L; 80 mg/d) and higher dose of PBLC (PBLC-H; 160 mg/d). Sheep in all groups were fed meadow hay ad libitum plus 600 g/d of concentrate pel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…They also reported that the responses of EOs to VFA concentrations may depend on the type of substrate consumed by ruminants and the pH of the rumen fluid. Patra et al (2019) found that doses of EO did not change the results of ruminal microbial fermentation, and that stable fermentation is maintained during minor microbial alterations as a result of metabolic redundancy of the ruminal ecosystem. More in vivo studies are needed to confirm our results.…”
Section: Rumen Fermentation Characteristics and Blood Metabolitesmentioning
confidence: 88%
See 2 more Smart Citations
“…They also reported that the responses of EOs to VFA concentrations may depend on the type of substrate consumed by ruminants and the pH of the rumen fluid. Patra et al (2019) found that doses of EO did not change the results of ruminal microbial fermentation, and that stable fermentation is maintained during minor microbial alterations as a result of metabolic redundancy of the ruminal ecosystem. More in vivo studies are needed to confirm our results.…”
Section: Rumen Fermentation Characteristics and Blood Metabolitesmentioning
confidence: 88%
“…The feed intake of lambs in the R500 group was lower, and this may be due to the intense aroma effect of EO, but the results for similar DM intake should also be evaluated. Low doses were noted to stimulate appetite and increase total feed intake per body weight (Patra et al 2019). Moroever, in vivo experiments are required to decide optimum dose levels, and low doses that have a stimulating effect (Patra 2016).…”
Section: Feed Intake and Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we found that the gut microbiota of rabbits with high finishing weight preferred to be involved in the biosynthesis of asparagine, cysteine, and arginine, but gut microbial communities in low finishing weight rabbits were more active in metabolizing tryptophan, tyrosine, and phenylalanine. Although asparagine is a non-essential amino acid, emerging evidence has demonstrated that it plays a key role in attenuating intestinal injury and improving the energy status of enterocytes, all of which are good for the health and growth of animals (Wang et al, 2015;Patra et al, 2019). Cysteine is able to regulate the antioxidant status and expression of anti-inflammatory genes in intestinal cells, which exert beneficial effects on body weight gain in pigs and chickens (Dilger and Baker, 2007;Yang and Liao, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In livestock breeding, health-related traits are becoming a priority, while hematologic parameters are important to evaluate the health condition, feeding management and nutrition level of animal, and the variation hematologic traits are caused by genetic and non-genetic (e.g., breed, age, sex and management systems) (24). At present, the studies on sheep hematologic parameters mainly focus on nutrition level and breed (25)(26)(27). In this study, the hematologic traits were measured for 819 male Hu sheep aged 6 months under the same nutritional level and management conditions, and the descriptive statistics and heritability estimates were performed for these traits, the results shown the average values were within the reference ranges of sheep according to the previous studies (26), the coefficient of variation were >10%, suggesting that these indexes have a certain selection space in the Hu sheep population.…”
Section: Discussionmentioning
confidence: 99%